Some possible requirements to build up and develop Hai Phong to be a Northern coastal Regional science and technology centre - Tuan, Tran Anh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The Decision No. 865/QĐ-TTg issued by the Prime Minister dated on 10th July 2008 on the approval on the Northern Coastal Development Planning toward 2025 and vision to 2050 has identified the objective as “to develop the Northern Coastal to become an integrated economic zone (with industries, tourism and services...), which has an important role in socio-economic development of the country, especially to the marine economic development strategy of Vietnam. To promote the role of the Northern sea gateway of Vietnam, on the basis of the development of regional extensive technical infrastructure system, creating favorable conditions for economic development and environmental protection, combined economic development and defensive security, ensuring sustainable development of the whole region”. Located at the centre of the northern coastal zone, Hai Phong City has played a very important role in the socio-economic development of the whole region. In the new emerging context of development, the task assigned for Hai Phong science and technology (S&T) is to rise up to become a S&T centre of the region. In this article, we focused on some practical requirements for Hai Phong in the process of building and developing as to be the S&T centre of the Northern Coastal region. Code: 16100401